ANTIOXIDANT ACTIVITY OF N-HEXANE EXTRACT OF NUTMEG PLANTS FROM SOUTH ACEH PROVINCE - Binawati Ginting; Mustanir Mustanir; Hira Helwati; Lydia Septa Desiyana; Eralisa Eralisa; Rohmat Mujahid (Universitas Syiah Kuala, 2017)
Abstract. It has tested the antioxidant activity of n-hexane extract respective roots, bark, fruit and seed crops of nutmeg against DPPH. Each extracted by maceration method with n-hexane. The extraction of each plant nutmeg with n-hexane extract obtained yield of n-hexane respectively 8,35%; 81,5%; 11,89% and 55,63%. The result of the antioxidant activity of n-hexane extract of each plant nutmeg against DPPH with a concentration of 25 ppm, 50 ppm and 100 ppm is obtained IC50, respectively, are 0,216 ppm, 63,755 ppm, 43,998 ppm and 11,599 ppm and positive control vitamin C ( IC50 = 3,657 ppm). Vitamin C is a standard compound is more often used than butyl for very high antioxidant activity. The antioxidant activity increases from high to low at the roots, seeds, fruits and bark of plants nutmeg in a row. Based on data GC-MS chemical components of each successive extracts of roots, bark, fruit and seeds are 41, 41, 44, 43 components of secondary metabolites. The main components of each part of the plant based on data from GC-MS are a 5-Octadecanoic acid, linalool, eugenol, myristicin, methoxyeugenol. The compounds are thought to play an active role in inhibiting free radicals from DPPH. n-Hexane extract nutmeg plant potential as an antioxidant. Keywords:Nutmeg (Myristica fragrans Houtt), n-hexane extract, Antioxidant, DPPH